IoT-Based Smart Classroom Prototype Using NodeMCU and Blynk for Environmental Monitoring - Zilni, An; Wibisono, Iwan Setiawan (Journal of Information System and Informatics, 2025)
The rapid advancement of the Internet of Things (IoT) has introduced numerous innovations in the education sector, one of which is the Smart Classroom concept a learning environment where interconnected devices communicate autonomously to enhance comfort, energy efficiency, attendance accuracy, and classroom safety. This study aims to design and implement an IoT-based Smart Classroom prototype utilizing NodeMCU as the main controller and the Blynk application as the platform for real-time monitoring and control of classroom conditions. Through this system, teachers and students can monitor temperature and humidity levels via mobile devices and remotely activate lights or fans without physically being in the classroom. The research employs a prototyping method comprising requirement analysis, design, implementation, testing, and evaluation to ensure that the system functions effectively and is user-friendly in a school setting. Experimental results demonstrate that the prototype operates reliably, displaying sensor data in real-time and performing automatic control actions such as activating the fan when the temperature exceeds a predefined threshold. Additionally, the system provides automatic alerts to maintain safety and comfort. Overall, the developed prototype offers a practical, low-cost, and easily deployable Smart Classroom solution that can be further enhanced through integration with online learning systems or data analytics for improved energy efficiency and sustainability.